Design of a Traffic Microsimulation in UML - Ortis, Genia (Communications - Scientific letters of the University of Zilina, 2019)
From the programming point of view traffic microsimulations consist of concurrent, interacting processes. Several representations of the same type (i.e. a car) are simulated over time. This structure highly corresponds to the concept of object oriented programming, which is therefore the first choice for the implementation of a traffic microsimulation. However, object oriented software has to be designed througly before the first line of program code is writen. Otherwise, with the expansion of the software and the increase of the number of developers a serious danger of incompatibilities and incorrect model behaviour arises. There exists a standard to describe object oriented models, the Unified Modelling Language UML. It can be used to describe a software from different points of view and therefore facilitates acquaintance and coordination processes and even code generation. In this paper I give an introduction into UML especially for developers of traffic microsimulations.